PENGARUH PENGGUNAAN ALAT PEMANGGANG TERHADAP KUALITAS ROTI TAWAR - Yundi, Silvinia; Elida, Elida; Syarif, Wirnelis (Journal of Home Economics and Tourism, 2017)
In this study aims to analyze the effect the effect of using the grill on the quality of bread which include external quality (volume, shape, color) and internal quality (texture, aroma and flavor). This type of research is pure experimentation (true experiment) with a completely randomized design methods, the research object is white bread. This study includes two variables X1 (gas oven), X2 (electric oven). The primary types of data are sourced from the five expert panelists and answer format organoleptic test. Data were analyzed using independent sample t test. The results showed that there is significant influence of the two different tools to the quality of bread, because Thitung> Ttabel. Volume 2.690> 2.306), (Form neat 6.396> 2.306), (4,333 square shape> 2.300), (skin color 3.244> 2.306), (tesktur softness 2.921> 2.306), (Texture elasticity 3.500> 2.306), (Smoothness pores pore 2.309> 2.306), (Texture uniformity of the pore 2,449> 2,306), (Aroma yeast 2.667> 2.306), (scent 3.182> 2.306) and (Rasa 4.427> 2.306)Keywords: Baking Tools, Quality, White Bread